2017
DOI: 10.1039/c7md00248c
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-targeted betulinic and ursolic acid derivatives: synthesis and anticancer activity

Abstract: Conjugation of native triterpenoids, namely, betulinic and ursolic acids, with a lypophilic triphenylphosphonium cation led to the dramatic enhancement, as compared to betulinic acid, of their ability to trigger the mitochondrial apoptosis pathway in various types of cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 40 publications
(35 reference statements)
1
24
0
1
Order By: Relevance
“…Spivak et al reported the synthesis of BN- and BA-based triphenylphosphonium derivatives [89,90,91,92]. For instance, BA-based triphenylphosphonium salt 175 was synthesized from 2β-allyl-BA methyl ester 172 (this compound was synthesized through a similar procedure to the one described in Scheme 17 [57]) as follows (Scheme 40): compound 172 underwent hydroboration with BH 3 ·THF, in THF to obtain diol 173 in 55% yield.…”
Section: Miscellaneous Methodologiesmentioning
confidence: 99%
“…Spivak et al reported the synthesis of BN- and BA-based triphenylphosphonium derivatives [89,90,91,92]. For instance, BA-based triphenylphosphonium salt 175 was synthesized from 2β-allyl-BA methyl ester 172 (this compound was synthesized through a similar procedure to the one described in Scheme 17 [57]) as follows (Scheme 40): compound 172 underwent hydroboration with BH 3 ·THF, in THF to obtain diol 173 in 55% yield.…”
Section: Miscellaneous Methodologiesmentioning
confidence: 99%
“…Two of the conjugates derived from ursolic acid and betulinic acid indicated a good range of IC 50 values. Compound 17 ( Table 4 ) derived from UA was obtained by the alkylation of the carboxyl group, C-28 of UA, with triethylene glycol dibromide in dimethylformamide (DMF) using K 2 CO 3 at 50 °C for 3 h [ 159 ]. Jiang et al synthesized a series of UA derivatives as inhibitors of Nuclear factor kappa B (NF-κB) by introducing long-chain amide moieties at the C-28 position, and the β-hydroxy group C-3 was protected by an acetyl group.…”
Section: Chemistry Of Uamentioning
confidence: 99%
“…This property of triterpenes is widely used in the synthesis of new therapeutic agents that, among other things, have a targeted effect. In particular, a popular trend is the creation of synthetic hybrids based on triterpenes and mitochondria-targeted delocalized cations, which can be used to modulate the activity of membrane proteins and enzymes of these organelles [ 2 , 3 , 4 , 5 , 6 ]. It is well known that mitochondria not only support the functioning of healthy cells, but are also involved in neoplasia and differentiation of cancer cells [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the poor water solubility of these triterpenes requires the use of high concentrations to accumulate in mitochondria and achieve the desired therapeutic effect, and this may cause numerous side effects that limit their use in clinical medicine. At the same time, triphenylphosphonium (or Rhodamine B)-linked triterpenoid derivatives show a much higher antitumor activity, inducing mitochondria-mediated apoptosis of tumor cells [ 2 , 3 , 4 , 5 , 6 ]. One of the promising penetrating cations showing mitochondrial targeting is the lipophilic delocalized F16 cation exhibiting anticancer activity in the free form [ 22 ], which, however, is manifoldly enhanced upon hybridization with triterpenes.…”
Section: Introductionmentioning
confidence: 99%